EFEKTIVITAS IMPLEMENTASI CORPORATE SOCIAL RESPOSIBILITY PT. ABC - Rizkiaji Rikky Djunaedi; Lukman M. Baga; Diah Krisnatuti (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2015)
The purposes of this study were 1) to analyze public perceptions on the effectiveness of the implementation of CSR of PT. A B C; 2) to analyze the implementation of CSR activities by PT. A B C; 3) to formulate strategies to improve the effectiveness of the implementation of CSR of PT. A B C. The method used in this research was descriptive analysis with a survey approach to measure expectations and performance assessment on the CSR implemented programs by the public, and there were respondents 104 respondents involved in this study. This study used the Importance-Performance Analysis (IPA) aiming to determine the effectiveness of the programs that have been implemented and to map the relationship between the expectations and the performance of each variable. Furthermore, using a SWOT analysis of the data processing and of the objectives of the program made by CSR is expected to provide recommendations to develop strategies in order to increase the effectiveness of CSR program of ABC Company.Keywords: corporate social responsibility (CSR), mining industry, implementation analysis, IPA, SWOTAbstrakTujuan dari  penelitian ini adalah 1) menganalisis persepsi masyarakat teradap efektivitas implementasi CSR PT. ABC; 2) menganalisis pelaksanaan  kegiatan CSR oleh PT. ABC; 3) merumuskan strategi untuk meningkatkan efektivitas implementasi CSR PT. ABC. Metode yang digunakan dalam penelitian ini adalah analisis deskriptif dengan pendekatan survey untuk mengukur harapan dan penilaian kinerja oleh masyarakat atas program CSR yang diterapkan. Jumlah responden sebanyak 104 orang.  Dalam penelitian ini digunakan Analisis Importance-Performance Analysis (IPA) bertujuan untuk mengetahui efektifitas dari program-program yang telah dijalankan serta  memetakan hubungan antara harapan dengan kinerja dari masing-masing variabel. Selanjutnya menggunakan analisis SWOT dari hasil pengolahan data dan dari tujuan program dibuat oleh CSR sehingga dapat memberikan rekomendasi untuk menyusun strategi dalam usaha meningkatkan efektifitas program CSR PT. ABC.Kata kunci: corporate social responsibility (CSR),industri pertambangan, analisis implementasi, IPA, SWOT